تأثير المستخلص المائي للحاء نبات القرفة في بعض معايير الخصوبة عند ذكور الأرانب المحلية - Morra, Mohamed; Jabbour, Rami; Soliman, Sousan (Latakia University Journal -Biological Sciences Series, 2018)
The present study aimed toevaluatethe effect of aqueous extract of cinnamon plant Bark on some parameters of fertility in the local male rabbits.15adult male rabbits divided into three groups of five each were used. Group 1 (control) was received normal food and water for a period of ten weeks while group 2 and three received orally a dose of aqueous plant bark extract (100 mg/b.w) and 200 mg/k.y/b.w. respectively, daily for ten weeks also.In the end of experience, blood samples were takenfortestosterone concentration in blood serum, and testis were excised and their weights and lengths were measured. Sperm count in the sementakenfrom the caudle epididymis wasdone using Hemocytometer. In addition, the motility and morphological abnormalities of spermswere assessed. The results showed a significant increase in the concentration of testosterone hormone in the experimental groups (P˂0.01) comparing to the control. In addition, a significant increase in the mean of testis weights and lengths (P˂0.01) was also noted.The study also showed a significant increase in the sperm count (P˂0.01), and also in their motility in the experimental groups (P˂0.01) and a decrease in the morphological abnormalities comparing to control group. هدفت الدراسة الحالية لتقصي تأثير المستخلص المائي للحاء نبات القرفة على بعض معايير الخصوبة عند ذكور الأرانب المحلية.أجريت الدراسة على 15من ذكور الأرانب البالغة، وزعت في ثلاث مجموعات: المجموعة الأولى (الشاهدة). قدم لها الماء والغذاء فقط، في حين جرعت المجموعتان الثانية والثالثة بجرعات من المستخلص النباتي قدرها 100مغ و200 ملغ / كغ من وزن الجسم على الترتيب، لمدة عشرة أسابيع. في نهاية التجربة، خدرت الحيوانات وتم سحب الدم من الوريد الحافي الأذني لمعايرة التستوستيرون، ثماستؤصلت الخصى وتم قياس أوزانها وأطوالها، وأخذ السائل المنوي من البربخ، وتم عد النطاف باستخدام شريحة نيوبورHemocytometer ثم قياس حركيتها، واحتساب النسبة المئوية للتشوهات الشكلية فيها. أظهرت نتائج الدراسة زيادة معنوية في متوسطات تراكيز هرمون التستوستيرون في المجموعتين التجريبيتين (P˂0.01) وتحسن معنوي في أوزان الخصى وأطوالها (P˂0.01)،وفي تعداد النطاف وحركيتها (P˂0.01)،مقارنة مع المجموعة الشاهدة. كما أظهرت الدراسة انخفاضاً معنوياً (P˂0.01 )في نسبة التشوهات الشكلية للنطاف في العينات المأخوذة من المجموعات التجريبية التي جرّعت بمستخلص نبات القرفة المائي مقارنةً مع المجموعة الشاهدة.